African Development: Beyond Income Convergence - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
In examining some big questions on African development, we provide evidence that dynamics of some development indicators could support both endogenous and neoclassical growth theories in the convergence debate. This paper investigates convergence in real per capita GDP and inequality adjusted human development in 38 African countries, disaggregated into 10 homogenous panels based on regions (Sub-Saharan and North Africa), income-levels (low, middle, lower-middle and upper-middle), legal-origins (English common-law and French civil-law) and religious dominations (Christianity and Islam). The main finding is that the income component of the human development index moves slower than others in the convergence process and thus requires a more focused policy intervention. As a policy implication, looking beyond income convergence can provide a concrete agenda for development involving all aspects of economic, institutional and social life.
Keywords: O11; O20; O47; O55; P52; 330; Human development; Growth; Convergence; Panel; Africa